ISOLATION AND CHARACTERIZATION OF ENDOPHYTIC MOLDS ON LEAVES AND STEMS OF TEA MISTLETOE (Scurrula atropurpurea (Bl.) Dans) - Maidhatul Rosidha Widyanti; Nour Athiroh Abdoes Sjakoer; Nurul Jadid Mubarakati; Fatimah Fatimah (El-Hayah, 2022)
Mistletoe tea is a parasitic plant that lives on its host, and this plant has potential as an herb. The tea plant parasite has several metabolites, namely alkaloids, flavonoids, terpenoids, glycosides, triterpenes, saponins, and tannins. The metabolite compounds produced by endophytic fungi have potential as herbs. Metabolite compounds are not only produced by mistletoe tea but are also produced by endophytic molds. This research aimed to isolate and characterize endophytic molds macroscopically and microscopically. This research uses an descriptive methods. Plant samples using mistletoe tea (Scurrula atropurpurea (Bl.) Dans) with the stages of sampling, making PDA media, isolation of endophytic molds, purification and macroscopic and microscopic characterization. Endophytic fungi that have been isolated were characterized by macroscopic and microscopic characterization. The results of the macroscopic and microscopic characterization research showed that seven isolates of mold were successfully isolated and characterized. Microscopic characterization found five different genus among the molds Alternaria sp., Penicillium sp., Aspergillus sp., Cladosporium sp. and Fusarium sp